Analisis Komunikasi Pemasaran Digital dalam Upaya Meningkatkan Omzet Perusahaan Konstruksi Pada CV. Mitra Tangguh Rekacipta - Dania Isnaeni Maulidia; Febrina Hambalah; Setya Prihatiningtyas (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2023)
The emergence of increasingly sophisticated digital tools has begun to shift almost all users of conventional marketing tools. The world of business and business or other life will not run as it should without communication. Construction companies are one of the industries that are experiencing the impact of the sophistication of digital tools. Without exception the company CV. Mitra Tangguh as one of the contractor companies in Surabaya. CV. Mitra Tangguh Rekacipta uses digital marketing as a form of marketing communication to boost sales of services from the company. The digital marketing used is Instagram, Whatsapp. website and e-mail. In this case digital marketing carried out by CV. Mitra Tangguh Rekacipta has affected the company's turnover. The research technique used is a qualitative case study method with the aim of obtaining a complete and in-depth description. Data collection techniques researchers conducted observations and interviews with objects and informants. The results obtained are increased turnover obtained from marketing communications CV. Mitra Tangguh Rekacipta has not been effective due to a lack of companies taking advantage of digital marketing opportunities.